THE USE OF PORPE (PREDICT, ORGANIZE, REHEARSE, PRACTICE, EVALUATE) STRATEGY IN TEACHING READING DESCRIPTIVE TEXT FOR THE TENTH GRADESTUDENTS OF SMAN 1 PERCUT SEI TUAN - Sakinah Rahma Hasibuan; Masitowarni Siregar; Safrida Lubis (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2020)
This study aims to find out the use of PORPE strategy in teaching reading descriptive text for the tenth grade students of SMAN 1 PercutSei Tuan in the academic year of 2019/2020. This study was conducted by using descriptive qualitative research. The data of this study were collected by using observation and interview to the process of PORPE strategy in teaching reading descriptive text and students’ self-predicted essay questions and answers as supported data. The result of observation, interview, and students’ self-predicted essay questions and answers prove that the use of PORPE strategy in teaching reading descriptive text for the tenth grade students of SMAN 1 PercutSei Tuan was 87%. Based on the result, the use of PORPE strategy which was done by the teacher were well-structured. Thus, the reason why PORPE considered to be applied because PORPE is appropriate in teaching reading descriptive text. The strategy made students more critical towards the questions because in every step they had to think critically and remember all the key points in the passage. The data were analyzed by using Sugiyono (2008) theory. It was supported that the percentage of each steps of PORPE strategy were predict (89%), organize (83%), rehearse (67%), practice (100%), and evaluate (100%). This showed that the students were interested in PORPE strategy and the average of students’ score of self-predicted essay questions and answers was 91. This number is categorized as good according to Nurgiyantoro’s Criterion Referenced Evaluation. Thus, PORPE strategy is effective and appropriate to be used in reading text, particularly descriptive text.Keywords: PORPE strategy, reading, descriptive text.